Artificial Intelligence – a new leap in international justice? Applying AI in the ECtHR - Yaroshenko, Maksym (Riga Graduate School of Law, 2024)
Technology, international law, and international justice have all sustained revolutionary changes on the edge of 20th and 21st centuries, redefining the world we live in. Two out of its paramount achievements – Artificial Intelligence and system of international justice, both developed uninterrupted in parallel, yet not being able to benefit from each other. The thesis aims at accessing theoretical and practical proposals on how to merge this fields, cantered around the case study of the European Court of Human Rights, suffering from structural challenges unsolved with the Interlaken reform process. ECtHR sets up a general framework against which the application of Judicial AI is tested to access its applicability as an auxiliary support system, and a uniform algorithmic dispute resolution mechanism (G.W. Leibniz and P.-S. Laplace), in pursuit of enhancing access to international justice, augmenting protection of human rights and cornerstone legal principles (i.e. equality, consistency and rule of law).
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law; European Court of Human Rights; Artificial intelligence; International Judiciary; Research Subject Categories::LAW/JURISPRUDENCE::Procedural law